Evaluation of the efficacy of percutaneous spinal cord stimulation according to the single or double leads - Esra Ertilav; Osman Nuri Aydin (Egyptian Journal of Neurosurgery)
Abstract Aim The aim of the study was to compare the efficacy of single or double lead in percutaneous spinal cord stimulation (SCS). Method Follow-up data of 41 patients (20 patients with double lead, 21 patients with single lead) who underwent percutaneous SCS were analysed. Demographic and clinical examination findings (gender, age, pain characteristic, neurological examination, medications used) and visual analogue scale (VAS) scores were recorded. VAS pain scores, clinical and neurological examination and complication findings were recorded at 1st and 12th months at post-procedure follow-up. Results Twenty patients had double lead and 21 patients had single lead. Five patients had root avulsion, 1 patient had complex regional pain syndrome, 1 patient had postherpetic neuralgia, 2 patients had phantom pain, 3 patients had ischaemic pain and 29 patients had postlaminectomy syndrome. In 10 patients, leads were placed in the cervical region and in 31 patients in the thoracic region. There was at least 50% reduction in VAS scores in 71.4% (15 patients) with single lead implantation and 65% (13 patients) with double lead implantation (p = 0.7). Infection was significantly higher in patients with double lead than in patients with single lead implantation (p < 0.05). In 1 patient, generator exchange was performed because the generator was exposed due to skin necrosis. No major complication was recorded. Conclusion SCS with single and double lead is an effective method in chronic pain syndromes. SCS with single lead can be preferred in terms of time, cost and labour saving.